Prediction of Damage Accrual in Systemic Lupus Erythematosus Using the Systemic Lupus International Collaborating Clinics Frailty Index. Issue 4 (12th February 2020) - Legge, Alexandra; Kirkland, Susan; Rockwood, Kenneth; Andreou, Pantelis; Bae, Sang‐Cheol; Gordon, Caroline; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Wallace, Daniel J.; Bernatsky, Sasha; Clarke, Ann E.; Merrill, Joan T.; et al.
Abstract : Objective: The Systemic Lupus International Collaborating Clinics (SLICC) frailty index (FI) has been shown to predict mortality, but its association with other important outcomes is unknown. We examined the association of baseline SLICC FI values with damage accrual in the SLICC inception cohort. Methods: The baseline visit was defined as the first visit at which both organ damage (SLICC/American College of Rheumatology Damage Index [SDI]) and health‐related quality of life (Short Form 36) were assessed. Baseline SLICC FI scores were calculated. Damage accrual was measured by the increase in SDI between the baseline assessment and the last study visit. Multivariable negative binomial regression was used to estimate the association between baseline SLICC FI values and the rate of increase in the SDI during follow‐up, adjusting for relevant demographic and clinical characteristics. Results: The 1, 549 systemic lupus erythematosus (SLE) patients eligible for this analysis were mostly female (88.7%) with a mean ± SD age of 35.7 ± 13.3 years and a median disease duration of 1.2 years (interquartile range 0.9–1.5 years) at baseline. The mean ± SD baseline SLICC FI was 0.17 ± 0.08. Over a mean ± SD follow‐up of 7.2 ± 3.7 years, 653 patients (42.2%) had an increase in SDI. Higher baseline SLICC FI values (per 0.05 increase) were associated with higher rates of increase in the SDI during follow‐up (incidence rate ratio [IRR] 1.19 [95% confidence interval 1.13–1.25]), after adjusting for age, sex, ethnicity/region, education, baseline SLE Disease Activity Index 2000, baseline SDI, and baseline use of glucocorticoids, antimalarials, and immunosuppressive agents. Conclusion: Our findings indicate that the SLICC FI predicts damage accrual in incident SLE, which further supports the SLICC FI as a valid health measure in SLE.